One Pot Mechanochemical Synthesis of Resorcinol Based Calix[4]arene and It’s ab initio Study - ABBASI, SHAHRYAR; NAGHIPOOR, ALI (Asian Journal of Chemistry, 2010)
One pot mechanochemical synthesis of calix[4]arene resorcinol with 12 OH groups has been synthesized and confirmed on the basis of IR, 1H NMR, 13C NMR and elemental analysis. Ab initio molecular orbital calculations at HF/3-21G*, HF/6-31G** and B3LYP/6-31G** levels of theory for geometry optimization are reported for the synthesized resorcinol based calix[4]arene.